Application of Absolute Alcohol in the Treatment of Traumatic Intracranial Hemorrhage via Interventional Embolization of Middle Meningeal Artery - Fan, Gangxian; Wang, Henglu; Ding, Jinke; Xu, Chao; Liu, Yongliang; Wang, Chao; Li, Zefu (Frontiers in Neurology, 2020)
Background: Intracranial hematoma is a common disease in neurosurgery; however, studies have reported problems such as high re-expansion rates after conservative treatment of epidural hematoma and high postoperative recurrence rates of subdural hematoma. Solutions to these problems are lacking, and research into new treatment methods is ongoing. Among the potential new treatments, middle meningeal arterial embolization is an option. This study involved patients with acute epidural hematoma and chronic subdural hematoma. The purpose was to evaluate the use and effects of absolute alcohol to embolize the middle meningeal artery to treat intracranial hematoma. Material and Methods: A retrospective description study was twelve cases of intracranial hematoma who treated with absolute alcohol interventional therapy from our hospital between June 2018 and October 2019. Five patients with acute epidural hematoma and seven patients with chronic subdural hematoma were treated using absolute alcohol to embolize the middle meningeal artery. Patients' clinical data, imaging results, surgical results, and prognosis were recorded and analyzed. Results: All patients underwent absolute alcohol embolization of the middle meningeal artery, in combination with burr-hole drainage. All imaging data were confirmed preoperatively. We successfully used absolute alcohol to embolize the middle meningeal artery intraoperatively and confirmed these results by postoperative angiography. All patients achieved symptomatic relief without complications, and no recurrence or re-expansion was seen with follow-up computed tomography. Our study has been registered in the Chinese Clinical Trial Registry (http://www.chictr.org.cn, ChiCTR1800018714). Conclusion: The use of absolute alcohol to embolize the middle meningeal artery could be used as an attempt to treat acute epidural hematoma and chronic subdural hematoma.